Fabrication of Counter Electrode for Dye Sensitized Solar Cells Application Using Environmentally Friendly Graphene and Carbon Nanotubes Composite Materials - Fatiatun Fatiatun; Nugroho Prasetya Adi (Universitas Sultan Ageng Tirtayasa, 2022)
In this research, carbon nanotubes (CNTs) was composited with graphene for counter electrode (CE) in dye sensitized solar cells (DSSCs) application. CNTs used were derivated from waste of palm oil that were environmentally friendly. The composited graphene and CNTs were fabricated on fluorine tin oxide (FTO) substrates by spray coating method. The aims in this study to improve electrical conductivity of CE which graphene hybrided with CNTs. Graphene oxide (GO) with home-made triple-tails sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-silphonate (TC14) surfactant (TC14-GO), reduced GO (TC14-rGO) and hybrid of TC14-rGO with CNTs (TC14 rGO-CNTs hybrid) were fabricated for CE in DSSCs application. Based on four-point probe measurement, the TC14 rGO-CNTs hybrid presented high electrical conductivity of 6.8 x 10-1 S.cm-1. This consistent with solar simulator result that TC14 rGO-CNTs hybrid as CE sample showed high efficiency of 0.0132%.